DESIGN, DEVELOPMENT AND HYBRID IMPEDANCE CONTROL OF AN ANKLE REHABILITATION ROBOT - Yildirim, Emre; Aktan, Mehmet Emin; Akdogan, Erhan; Misirlioglu, Tugce Ozekli; Palamar, Deniz (WORLD SCIENTIFIC PUBL CO PTE LTD, 2025)
In this study, a hybrid impedance control-based portable ankle rehabilitation robot that can perform therapeutic exercises for the ankle has been developed. This 1-DOF robot can perform plantar flexion and dorsiflexion movements for the ankle. The capacity of the robotic system to perform therapeutic exercises was tested with subjects. Isotonic and resistive exercises were tested with 10 healthy subjects and stretching exercise was tested with a patient. The results showed that the hybrid impedance controlled robotic system can successfully perform passive stretching, active isotonic and active resistive exercises by providing a safe human-robot interaction. Especially when a sudden resistance increase occurs in the joint, the hybrid impedance controller acts like a physiotherapist and performs the movement without damaging the joint.
Keywords: Ankle rehabilitaton; hybrid impedance control; rehabilitation robot; human-robot interaction; Biophysics; Engineering